Gamify Your Teaching - Using Location-Based Games for Educational Purposes - Erenli, Kai (International Journal of Advanced Corporate Learning (iJAC), 2013)
Gamification has become a hot topic for todayâ??s educators. Many tools and methods have been developed and students have got used to Foursquare or Barcoo. This paper introduces an easy and cost-effective method that educators can use to develop custom-made Scavenger Hunts which meet the needs and expectations of their various fields. In fact, the method can be used for multiple purposes, topics and audiences: elementary school children can be addressed as well as adult workers. The only devices needed to deploy the method are a QR-code-scanning device (such as a smartphone) and a GPS device. It must also be considered that almost 50 per cent of the U.S. population owns a smartphone. As a consequence our method â?? called â??QuizeRoâ? â?? can be considered easy to use. It is also expected to make teaching more fun. The paper will offer a toolkit for individual use and a how-to guide based on the presenterâ??s own research and experience. A best practice case will also be presented to illustrate the impact on education. Moreover the paper will address advantages of learning in a playful setting and will outline further steps to quantify the outcome of this specific method.